Enhancing Perinatal Safety with the Advancement of Obstetric Anesthesia in Japan - Reiko Ohara (Women's Health Reports)
Japan is one of the most developed countries in the world, and perinatal care is safe, with low maternal and neonatal mortality rates. However, as birthrate declines, advanced maternal age and the number of cesarean deliveries increases, efforts must be made to maintain safety in the future. The characteristic of the delivery facilities is “many small clinics,” and half of all facilities have fewer than 500 deliveries per year. Such clinics rarely have full-time anesthesiologists; therefore, anesthetic management, including cesarean deliveries and labor analgesia, is left to obstetricians’ efforts. Furthermore, the prevalence of labor analgesia is very low compared with that in developed countries. In 2017, maternal deaths during labor analgesia were reported and became a social problem. The Ministry of Health, Labor, and Welfare (MHLW) appointed a research group to conduct a study on labor analgesia and issued recommendations for a safe delivery system in 2018. Even when recommendations are understood, changing the size and staffing of medical facilities is challenging, and the field needs specific interventions such as education and information sharing. Most maternal deaths related to anesthesia are preventable. Within the existing medical environment, a distinctive anesthetic management system is crucial to improve the safety of perinatal care, and cooperation among obstetricians, anesthesiologists, nurses, and midwives involved in perinatal care through education and management is essential. We review past perinatal safety initiatives in Japan and discuss the need to make obstetric anesthesia safer as future risks increase.